Racial Differences in the Incidence of and Risk Factors for Atrial Fibrillation in Older Adults: The Cardiovascular Health Study. Issue 2 (15th January 2013) - Jensen, Paul N.; Thacker, Evan L.; Dublin, Sascha; Psaty, Bruce M.; Heckbert, Susan R.
<x xml:space="preserve">Abstract</x> This study examined whether different associations between risk factors and atrial fibrillation (AF) according to race could explain the lower incidence of AF in blacks. Baseline risk factor information was obtained from interviews, clinical examinations, and echocardiography in 4, 774 white and 911 black Cardiovascular Health Study participants aged 65 and older without a history of AF at baseline in 1989/90 or 1992/93. Incident AF was determined according to hospital discharge diagnosis or annual study electrocardiogram. Cox regression was used to assess associations between risk factors and race and incident AF. During a mean 11.2 years of follow‐up, 1, 403 whites and 182 blacks had incident AF. Associations between all examined risk factors were similar in both races, except left ventricular posterior wall thickness, which was more strongly associated with AF in blacks (per 0.2 cm, blacks: hazard ratio (HR) = 1.72, 95% confidence interval (CI) = 1.44–2.06; whites: HR = 1.30, 95% CI = 1.18–1.43). Overall, the relative risk of AF was 25% lower in blacks than whites after adjustment for age and sex (HR = 0.75, 95% CI = 0.64–0.87) and 45% lower after adjustment for all considered risk factors (HR = 0.55, 95% CI = 0.35–0.88). Different associations of the considered risk factors and incident AF by race do not explain the lower incidence of AF in blacks.